(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The methods of carbon nanomaterial manufacture prevalent in the society at large, which mainly emphasized on usage of precursors based on fossil fuel or other carbon rich fuels. This motivates to search for an abundant and accessible material that furnishes the same needs. This brings to the basic raw material or precursor utilized i.e. oil seeds and plant fibers. The objective of this work is to analyze various types of oil seeds (e.g., sunflower, neem etc.), and plant based fibers (like palas, wheat husk, etc.) to synthesize carbon nanomaterials. Since these materials are solid, pyrolysis could be done without the use of any catalyst. If we succeed in this exploration, then production of carbon nanomaterial could be easy and economical. Keeping these ideas in mind selection of plant fibers and various oil seeds were made. These materials were pyrolysed at suitable temperature hence Morphology, when analyzed on a microscopic level, gives sharp grain like features which do not collapse in situ.